1999
DOI: 10.1182/blood.v94.2.684
|View full text |Cite
|
Sign up to set email alerts
|

Acute Systemic Reaction and Lung Alterations Induced by an Antiplatelet Integrin gpIIb/IIIa Antibody in Mice

Abstract: Shock is frequently accompanied by thrombocytopenia. To investigate the pathogenic role of platelets in shock, we examined the in vivo effects of monoclonal antibodies (MoAbs) against mouse platelet membrane proteins. Injection of the platelet-specific MoAb MWReg30 to the fibrinogen receptor (gpIIb/IIIa) rendered mice severely hypothermic within minutes. Isotype-matched control antibodies, even if they also recognized platelet surface antigens, did not induce comparable signs. MWReg30 induced early signs of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 43 publications
3
30
0
Order By: Relevance
“…Although antiplatelet antibodies can activate human platelets in vitro , causing platelet aggregation and degranulation (Horsewood et al ., 1991), we have failed to detect such aggregation (by means of aggregometry) using platelet‐rich plasma (PRP) exposed to various concentrations of OVA (data not shown). A similar nonresponsiveness of mouse PRP to a monoclonal antibody to fibrinogen receptors (gpIIb/IIIa) has also been reported by Nieswandt et al . (1999).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Although antiplatelet antibodies can activate human platelets in vitro , causing platelet aggregation and degranulation (Horsewood et al ., 1991), we have failed to detect such aggregation (by means of aggregometry) using platelet‐rich plasma (PRP) exposed to various concentrations of OVA (data not shown). A similar nonresponsiveness of mouse PRP to a monoclonal antibody to fibrinogen receptors (gpIIb/IIIa) has also been reported by Nieswandt et al . (1999).…”
Section: Resultssupporting
confidence: 82%
“…Thus, it is of particular interest to know whether this type of receptor is present on platelets in mice. In fact, murine platelets, have been reported to lack FcγRII (CD32) (Kato et al ., 1998), and Nieswandt et al . (1999) reported that mouse platelets were not stained by an anti‐FcγRII/III monoclonal antibody.…”
Section: Resultsmentioning
confidence: 97%
“…A newly generated mAb against mouse αIIbβ3 (JON/A, IgG2b) was used in the current study. JON/A, like the well‐established anti‐αIIbβ3 mAb MWReg30 (10), precipitated αIIbβ3 from the lysate of surface‐biotinylated platelets (Fig. 1a).…”
Section: Resultsmentioning
confidence: 92%
“…MWReg30 and p0p6 antibodies were generated, produced, and modified in our laboratories: MWReg30 (anti‐ αIIbβ3, IgG1; ref. 10) and p0p6 (anti‐GPIX, IgG1; ref. 11).…”
Section: Methodsmentioning
confidence: 99%
“…Pharmacology/toxicity of surrogate molecules. Administration of a surrogate anti‐murine GP IIb/IIIa antibody (MWReg30) to mice resulted in FcγRIII and TNF‐α‐dependent hypothermia, engorgement of alveolar septal vessels and acute lung injury (Nieswandt et al ., 1999). In vitro , MWReg30 inhibited platelet aggregation and did not induce morphological signs of platelet activation.…”
mentioning
confidence: 99%